An Analysis of Maxim Violation in Gibran di Antara Ganjar dan Prabowo-Rosi Podcast - Ninok Narindra; Zakiyatul Lathifah; Afiifah Al Rosyiidah (PRAGMATICA : Journal of Linguistics and Literature, 2026)
In effective communication, the speaker tries to follow certain rules to ensure the message is understood. This study will analyze a conversation from the YouTube video Gibran di Antara Ganjar dan Prabowo – ROSI  using the cooperative principles theory by Grice (1989), as explained in Yule (1996) Pragmatics. The aim of this research is to identify how participants, especially politician Gibran, follow or violate the four Gricean Maxims such as Maxim of Quantity, Maxim of Quality, Maxim of Relation, and Maxim of Manner. This study uses the qualitative method. This approach is chosen because the focus is on analyzing and interpreting the meaning and context of the language. The data studied comes from the conversation of the YouTube video Gibran di Antara Ganjar dan Prabowo – ROSI. The findings show that Gibran sometimes gives limited or vague answers that violating the maxim of Quantity and Manner, avoids the direct relevance to sensitive questions that violating the maxim of Relation, and speaks carefully to maintain truthfulness that partly following the maxim of Quality. These patterns reveal that his communication style mixes cooperation with strategic violations, reflecting how political figures use language to manage topics and protect their image in public discussions.